Hormone therapy and risk of myocardial infarction. (January 2009) - Lowe, Gordon
Evaluation of: Lokkegaard E, Andreasen AH, Jacobsen RK, Nielsen LH, Agger C, Lidegaard O: Hormone therapy and risk of myocardial infarction: a national register study. Eur. Heart J. 29(21), 2660–2668 (2008) . In a national register study of healthy women aged 51–69 years in Denmark followed between 1995 and 2001, 4947 incident myocardial infarction cases were identified. Overall, there was no increased risk of myocardial infarction in current hormone therapy users. However, an increased relative risk was observed in younger women (aged 51–54 years). Overall, the highest risk of myocardial infartion was found with continuous hormone therapy. There was no increased risk found with unopposed estrogen, cyclical combined therapy or tibolone. A lower risk was found with dermal route. However, no associations were found with progestogen type or estrogen dose.